A structural investigation of heteroleptic pentavalent antimonials and their leishmanicidal activity. (10th March 2016) - Mushtaq, Rabia; Rauf, Muhammad Khawar; Bond, Marcus; Badshah, Amin; Ali, Muhammad Irshad; Nadhman, Akhtar; Yasinzai, Masoom; Tahir, Muhammad Nawaz
Abstract : In the quest for new drug candidates for the safe treatment of parasitic diseases like leishmaniasis, a series of heteroleptic pentavalent antimonials of the type [SbR3 (OOCR′)2 ] were synthesized and characterized using elemental analysis, Fourier transforminfrared spectroscopy and multinuclear ( 1 H and 13 C) NMR spectroscopy. The carboxylate moieties are predominantly substituted benzoates with some complexes that fit in acetato or nicotinato ligands. The crystal structures of [Sb( p ‐Tol)3 ( p ‐CH3 C6 H4 COO)2 ], [Sb( p ‐Tol)3 (3, 5‐Cl2 C6 H3 COO)2 ] and [Sb( p ‐Tol)3 (3‐nicotinato)2 ] were determined crystallographically and shown to adopt geometriesintermediate between trigonal bipyramidal and square pyramidal, and essentially monomeric with a five‐coordinated Sb center. The leishmanicidal activity was assessed against the Leishmania tropica KWH23 parasite, and the cytotoxicity level was also measured on human macrophage blood cells. It was observed that IC50 of the antimonials was 100‐fold superior as compared with the standard antimonial drug used. Cytotoxicity results showed that these antimonials are highly active even at low concentrations and are biocompatible with human macrophages, making them highly promising drug candidates for further investigation. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Leishmanicidal activity and biocompatibility were assessed against Leishmania tropica KWH23 and human fibroblast blood cells, respectively. On the basis of significant ( p < 0.01) IC50 values, the compounds were found to be most potent in comparison with the standard Glucantime (4.4 ± 0.77μg ml −1 ).